THE OPTIMIZATION OF RURAL LANDSCAPE IN THE LIGHT OF THE IDEA OF SUSTAINABLE DEVELOPMENT – THE EXAMPLE OF POLAND - Sobala, Michał; Myga-Piątek, Urszula (Quaestiones Geographicae, 2016)
Contemporary rural landscapes in Poland are being changed intensively and adversely. These changes lead to landscape disharmony, spatial disorder, the blurring of individual and specific features and disruption to the ecological equilibrium. This article aims to present general rules for the optimization of rural landscapes. It discusses the causes and consequences of unfavourable changes within Poland’s rural landscapes which constitute a threat to their sustainable development. The authors attempt to identify the major factors to be considered in taking steps aimed at landscape optimization. Landscape equilibrium may be assessed through the sustainable development dimensions: ethical, ecological, social, economic, technical, political and legal. Landscape optimization consists in maintaining the balance within these dimensions.